Facial emotion perception in patients with epilepsy: A systematic review with meta-analysis. (December 2017) - Edwards, Michelle; Stewart, Elizabeth; Palermo, Romina; Lah, Suncica
Highlights: Patients with epilepsy have large deficits in facial emotion perception. Temporal and generalised epilepsy show different emotion-specific impairments. Younger age at testing is associated with lower facial emotion perception accuracy. Future research should include children and patients with extra-temporal epilepsy. Abstract: Facial emotion perception is a fundamental social competency relying on a specialised, yet distributed, neural network. This review aimed to determine whether patients with epilepsy have facial emotion perception accuracy impairments overall, or for a subset of emotions (anger, disgust, happiness, sadness, fear, and surprise), and the relationship to epilepsy type, demographic/treatment variables, and brain organisation. Database searches used PRISMA guidelines with strict inclusion/exclusion criteria. Thirty included studies assessed patients with temporal lobe (TLE; n = 709), frontocentral (FCE; n = 22), and genetic generalised (GGE; n = 48) epilepsy. Large deficits emerged in patients with epilepsy compared to controls ( n = 746; Hedges' g = 0.908–1.076). Patients with TLE were significantly impaired on all emotions except surprise; patients with GGE were significantly impaired in anger, disgust, and fear perception. Meta-regression of patients with TLE revealed younger age at testing was associated with lower accuracy. This review provides evidence for marked global deficits of emotion perception in epilepsy, with differential emotion-specific impairment patterns in patients with TLE and GGE.